Photocatalytic degradation of Rhodamine B dye by cotton textile coated with SiO2-TiO2 and SiO2-TiO2-HY composites - Landi Júnior, Salmon (2017)
This work is devoted to study the photocatalytic ability of cotton textiles functionalized with SiO2-TiO2 and SiO2-TiO2-HY composites to degrade a dye molecule. Coatings were prepared by sol-gel method and calcined at different temperatures in a range of 400–750 °C. FTIR confirmed the existence of SiOTi bounds and the band located in the region between 570 and 600 cm−1 was used to calculate the framework Si/Al ratio of HY in the SiO2-TiO2-HY composites. XRD confirmed the presence of nanosized TiO2 (anatase phase) in all calcined composites. Nitrogen adsorption isotherms showed a decrease in surface area and pore volume for higher calcination temperature. A simple mechanical process was used to impregnate the different composites on the cotton substrates. The photocatalytic activity of cotton textiles functionalized with SiO2-TiO2 and SiO2-TiO2-HY composites was tested via the degradation of Rhodamine B (RhB) dye under similar solar irradiation. The best catalytic performance was achieved with the SiO2-TiO2 and SiO2-TiO2-HY composites subjected to a calcination treatment at 400 °C, whereas SiO2-TiO2 presented a decolourization and mineralization around 94% and 89%, respectively, after 2 h of irradiation. Furthermore, the products of RhB degradation were analysed and identified by using HPLC-ESI–MS and ion chromatography techniques and a photocatalytic mechanism was proposed.